Protection, landscaping and regulation of agricultural land in Serbia - Popov, Danica (Zbornik radova Pravnog fakulteta u Novom Sadu, 2015)
The subject of this article is protection, landscaping and regulation on agricultural land, based on The Agriculture Land Law in Serbia.Land is besides water and air the basic component of the environment. Bearing in mind the long-term processes of creation and development, land is the conditionally renewable resources. Land use, particularly in agricultural production, there is often a balance disorder of certain factors, which inevitably leads of damage. Land is in the nature of a slow learner, but in the process of degradation quickly destroyed. The main impact on land, recognized in the EU and candidate countries include erosion, reduction in organic matter, contamination (local and diffuse), occupation of land by building (buildings road), compaction floods and avalanches, reduction of soil biodiversity and salinization. Inventory of the state of pollution and damage to land, the establishment of permanent monitoring and reporting system requirement for developing strategies and selection of measures of quality care and prevention of negative processes. The measures of landscaping in The Agricultural land Law are: linking of land plots, voluntary grouping of lad plots and melioration of land. The owner of agricultural land has an obligation to cultivate the land in accordance with the code of good agricultural practice, prescribed by the Law.